New Human Rights Issues. Understanding Their Contentious Rise - Clifford Bob (Universidad de Los Andes, 2009)
Why are certain problems recognized as human rights issues, while others are not? This article focuses on the political strategies through which marginalized groups transform long standingdomestic grievances into internationally-recognized human rights claims. Highlighting the interacting roles of aggrieved local groups, powerful gatekeepers in international human rights organizations, and state and civil society opponents, the article develops a four-stage model for the development of new human rights. The article also challenges constructivist theories about the formation of international norms development.